SEARCH FOR METHODS FOR SOLVING POLITICAL ISSUES IN THE SOUTH CAUCASUS - Hasan Siddik Karademir (Наука Красноярья, 2017)
This article highlights the most nodal contradictions taking place on the modern historical format between the political elites of Baku, Ankara and Yerevan. Passing the long history of diplomatic relations between Azerbaijan and Turkey, the author focused on the key issues of military doctrines and the policy of non-interference in the affairs of other states. It was found out that Azerbaijan and Turkey are united by linguistic, ethnographic and geographical factors. In turn, these countries are looking for peace with Armenia, so as to successfully implement their own political line.